Traveling: A Way to Freedom, Self-Discovery, and Spiritual Awakening in Rolf Potts’ Vagabonding: An Uncommon Guide to the Art of Long-Term World Travel - Koirala, Pashupati Raj (Literary Studies, 2026)
This paper explores how traveling is linked with human instinct, the love for freedom, and spiritual awakening. It highlights the fact that traveling is possible even with limited funds if a traveler has a passion to explore new things. For this purpose, Rolf Potts’s book Vagabonding (2002), which is a collection of stories, lessons, and excerpts on traveling, is selected. The writer focuses on the idea that it is better to live a story than to tell a story. In a globalized world, it is ironic that humans are trapped, confused, and disheartened under the immense pressure of time, money, and matter. Life is so rich and varied, yet humans are confined and manipulated by the growth of modern digital technology and social media. It seems as if we are too weak to view ourselves and others clearly. Traveling is the opportunity for self-discovery and gaining new and unexpected experiences. Traveling is not only about reaching the destination and taking photographs; it is also about being open-minded, humble, and inclusive. Moreover, it is about assimilating with new surroundings, their inhabitants, and their culture. This paper makes a significant contribution by bringing out the idea that traveling is more than visiting sophisticated places and capturing them in prints and paintings. It also brings forth other dimensions to which mainstream travel literature gives little attention.